Fish canning industry wastewater treatment for water reuse – a case study - Cristovão, Raquel (2015)
The valorization of wastewaters from the fish canning industry is of great concern, not only because of the high quantities generated, but also economic and environmental benefits may result from a proper treatment approach of the waste generated while reducing costs related to wastewater discharge. A limiting factor for reuse and recycling treated fish canning wastewater into an industrial plant and also for other uses is the high salt content, which persists even after conventional treatment. So, the reuse of fish canning industrial wastewater was assessed by combining conventional treatments, such as sedimentation, chemical coagulation-flocculation and aerobic biological degradation (activated sludge process) followed by a polishing step by reverse osmosis (RO) and ultraviolet (UV) disinfection. In this investigation all these processes were optimized in order to remove essentially the effluent suspended particles (primary treatment), the organic matter content in the biological aerated reactor (secondary treatment) and, finally, the remaining salts and microorganisms (tertiary treatment). The overall removal efficiencies obtained were: 99.9% for dissolved organic carbon (DOC), 99.8% for oil and grease (O&G), 98.4% for total suspended solids (TSS), above 96% for anions and cations and 100% for heterotrophic bacteria expressed as colony-forming units (CFU). The final clarified effluent was found to have the quality requirements to be recycled or reused in the industrial plant, allowing the reduction of the effluent to be discharged, the water use and the costs of tap water for industrial use. As regards the energy and chemicals costs, to obtain a treated effluent to be reused in the process costs 0.85 V/m3. This value can be reduced by about 60% if the goal is only to meet the legislated standards for the effluent discharge into water bodies. Tap water for the industrial plant costs about 2.1 V/m3.